The Challenges of EFL Teacher in Conducting Online Learning at SMA Candimas Pancasari - Luh Putu Rastiti Puspita Dewi; Putu Adi Krisna Juniarta; Ni Putu Astiti Pratiwi (Journal of Educational Study, 2021)
The purpose of this study was to determine the teachers' challenge in conducting online learning at SMA Candimas Pancasari The design of this research is descriptive qualitative. In this study, the challenges of teachers in online teaching were analyzed and described descriptively. The findings in this study are about the challenges of teachers in conducting online learning at SMA Candimas Pancasari and how to overcome the challenges. Internet connection is one of the main challenges in online teaching. Internet connection is influential in online learning because some teachers and students live in difficult signal areas. This poor internet connection makes online learning unable to be 100% effective. Teachers have ways of overcoming these challenges by way of offline (LURING) for some students who have problems and provide a schedule to come to school. Teachers can overcome these challenges with various strategies during online learning.